Deterministic seismic hazard analysis for Peshawar, Pakistan - Waseem, Muhammad; Khan, Mohammad Asif; Javed, Muhammad Waqas; Ali, Syed Mohammad (Journal of Himalayan Earth Sciences, 2013)
Ground motion estimation for a site (34.01oN, 71.45oE) located in the Peshawar in terms of Peak Ground Acceleration (PGA) values is conducted. It is carried out with deterministic seismic hazard analysis approach using faults sources within a radius of one hundred kilometers around site. The results of this study indicate that the Main Boundary Thrust located at a distance of twenty nine (29) kilometers from the site with a maximum potential moment magnitude of 8.1 is potentially the most seismogenic source for an earthquake in the region. Such a scenario earthquake may generate a design earthquake with PGA values of 0.232 g in Peshawar. PGA map for area surrounding the site (33.75o-34.15oN; 71.29o71.50oE) is also developed in this study. This map shows that the peak-ground acceleration values are highly variable around the site.